Linkages Between Community-Focused Agriculture, Farm Sales, and Regional Growth. (February 2014) - Brown, Jason P.; Goetz, Stephan J.; Ahearn, Mary C.; Liang, Chyi-lyi (Kathleen)
Community-focused agriculture has been heralded as a development strategy to induce local economic growth. This study examines county-level linkages between community-focused agriculture and growth in total agricultural sales and economic growth more broadly. Using Census of Agriculture data, regional growth models are estimated on real personal income per capita change between 2002 and 2007. We find no association between community-focused agriculture and growth in total agricultural sales at the national level, but do in some regions of the United States. A 1 increase in farm sales led to an annualized increase of 0.04 in county personal income. With few exceptions, community-focused agriculture did not make significant contributions to economic growth in the time period analyzed.